Characteristic on electromagnetic energy harvesting using graphene/silver filled epoxy for PVT thermal hybrid solar collector - Naroh, Azmi (2019)
Emerging wireless and flexible electronic systems such as wearable or portable devices and sensor networks call for a power source that is sustainable,reliable,have high power density,and can be integrated into a flexible package at low cost.These demands can be met using photovoltaic thennal (PVT) systems,consisting of solar modules for energy harvesting,battery storage to overcome variations in solar module output or load and often power electronics to regulate voltages and power flows.A great deal of research in recent years has focused on the development of high-performing materials and architectures for individual components such as solar cells panel circuit and batteries.The use of graphene and silver conductive ink as a flexible,low-cost solution-processed transparent electrode for photovoltaics is investigated.To fabricate these systems,conductive ink printing technique are of great interest as they can be performed at low temperatures and high speeds and facilitate customization of the components.The parameters that were evaluated consist of resistivity,surface roughness,and morphological analysis.In order to accomplish the analysis,the four-point probe is used to measure the resistance value of the sample in ohm-per-square.Conductive ink loading has detected the presence of resistivity with a certain percentage.The highest average resistivity is detected in 1 layer coil conductive ink while the low resistivity in 3 layers coils conductive ink.In terms of surface roughness, Nanoindentation machine was used which resulted that the samples with a consistent average value of uniform and smooth surface.Conductive ink samples with 80% weight percentage of filler had consistent surface regularities that contributed to smooth surface.In morphological analysis,nanoindentation is used to visualize the microscopic image of graphene and silver nanoparticles ink categorized by the electrical properties of the ink.